Transcutaneous cervical vagus nerve stimulation improved motor cortex excitability in healthy adults: a randomized, single-blind, self-crossover design study - Wang, Meng-Xin; Wumiti, Aihaiti; Zhang, Yao-Wen; Gao, Xue-Sheng; Huang, Zi; Zhang, Meng-Fei; Peng, Zhi-Yong; Oku, Yoshitaka; Tang, Zhi-Ming (Frontiers in Neuroscience, 2023)
Purpose: To investigate the effect of transcutaneous cervical vagus nerve stimulation (tcVNS) on motor cortex excitability in healthy adults.Method: Twenty eight healthy subjects were assigned to receive real and sham tcVNS for 30 minutes. The interval between the real and sham conditions was more than 24 hours, and the sequence was random. The central and peripheral motor-evoked potential (MEP) of the right first dorsal interosseous (FDI) muscle was measured by transcranial magnetic stimulation (TMS) before and after stimulation. MEP latency, MEP amplitude and rest motor threshold (rMT) were analyzed before and after stimulation.Results: MEP amplitude, MEP latency and rMT had significant interaction effect between time points and conditions (p<0.05). After real stimulation, the MEP amplitude was significantly increased (P<0.001). MEP latency (p<0.001) and rMT (p=0.006) was decreased than that of baseline. The MEP amplitude on real condition was higher than that of sham stimulation after stimulation (P=0.027). The latency after the real stimulation was significantly shorter than that after sham stimulation (p=0.005) . No significantly difference was found in rMT after stimulation between real and sham conditions (p>0.05).Conclusion: tcVNS could improve motor cortex excitability in healthy adults.